Set of Data Elements for Nautical Charts Cataloging: Analysis Between the RDA Scheme and the IDERA Metadata Profile - Stubbs, Edgardo (European Journal of Multidisciplinary Studies, 2018)
The nautical chart is a cartographic resource designed to meet the requirements of maritime navigation, showing the depth of the water and the nature of the seabed, as well as the configuration, features and elevation of the coast and the dangers and aids to navigation. The nautical charts provide a graphic representation of the information required by the navigator to carry out safe navigation. The organization and description of this type of resources is a key element when accessing information. From the scope of librarianship, the current scheme for the processing of information is the RDA standards Resource, description and access), which allow the description of all kinds of information resources. On the other hand, geospatial organizations have developed different specific metadata schemes for the processing of spatial information. Metadata allows a producer to describe a dataset fully so that users can understand the assumptions and limitations and evaluate the dataset’s applicability for their intended use. In Argentina, the scheme for processing this kind of information is called IDERA, which is based on the ISO 19115: Standards on geographic information. The present work analyzes the treatment that specific rules of metadata like IDERA and general norms of description of resources like RDA give to the set of specific data present in the digital nautical charts. Methodology: from the identification of data elements that allow to describe and identify nautical charts as information resources a comparative table between both schemes was developed. Results: Neither of the two schemes has contemplated the totality of data element set established for the identification of nautical charts. The RDA scheme managed to better satisfy the description and identification of nautical charts that IDERA, although neither of them contemplate 100 percent the established data elements set. Conclusions and recommendations: 1) According to the above, neither of the two schemes to process the information complies in its entirety with the information contained in the nautical charts. 2) Some data elements do not fit in any of the two schemes, reducing visibility and information retrieval of the two schemes for processing information, RDA are those that allow a more complete description of the resource, although in a general, non-specific way. 3) The specialized spatial data scheme (IDERA) leaves out important data elements of this kind of resources. 4) IDERA metadata profile, although it was thought for spatial data does not include the special characteristics of the different resources that make it up. 5) It is advisable to develop a metadata profile that, in addition to contemplating the general characteristics of geospatial resources, includes the particularities of each class of its resources